HOW TO ALLOW FOR USER-CENTERED INNOVATION OVER AN ESTABLISHED INFORMATION INFRASTRUCTURE WITHIN AN INSTITUTIONALIZED CONTEXT - Synnøve Thomassen Andersen (European Scientific Journal, ESJ, 2014)
This paper describes a user-centered innovation process within psychiatric services for children and adolescents, implementing a new decentralized model in rural areas in Norway by using mobile phone technology. We apply theory of information infrastructures as a frame of reference for analysing what enables or constrain user-centered innovation processes within a complex organizational context. We illustrates what roles the various levels of an information infrastructure and its installed base can play in innovation processes, implying a complex interplay between technical, organizational and institutional factors. We argue that as a result of this user-centered innovation, the new model emerged with a larger potential for creating a new innovation path than would have been the case if it had been linked to the existing structures. The aim of this paper is thus to contribute to the understanding of how to allow for user-centered innovation over an established information infrastructure within an institutionalized context.